KAJIAN STUNTING PADA ANAK BALITA DITINJAU DARI PEMBERIAN ASI EKSKLUSIF, MPASI DAN STATUS IMUNISASI DI KELURAHAN ALAK KOTA KUPANG - Estiyani Wulandari; Hironima Niyati Fitri (Jurnal Maternitas Kebidanan, 2023)
Stunting is one of the serious public health problems, especially in developing countries. Stunting is a condition of growth failure that can affect children under five and have a long-term impact on physical and cognitive development. According to data from the World Health Organization (WHO), around 149 million children worldwide suffered from stunting in 2020. Indonesia is also inseparable from this problem, with the stunting rate still quite high. Kupang City is one of the regencies/cities in East Nusa Tenggara (NTT) that is included in the priority city for handling stunting. Based on the results of nutritional status monitoring in Kupang City in 2022, the number of toddlers is 25. 543 toddlers, short or stunted as many as 5,497 (21.5%) toddlers, consisting of 4,075 short and 1,422 very short. Alak Village is one of the villages that is included in the priority of stunting handling in Kupang City with 180 stunting toddlers. The purpose of the study to examine the incidence of stunting in children under five was reviewed by exclusive breastfeeding, MP-ASI, and immunization status. The quantitative research approach was designed as a Case Control Study, and was conducted in Alak Village, Kupang City with a total of 35 case and control samples. The data collected includes primary and skunder data. Data analysis included univariate and bivariate using Chi-Square Test at 95% CI, as well as multivariate using logistic regression. The results of the study obtained the incidence of stunting in toddlers due to non-exclusive breastfeeding (p = 0.000; OR=8,000), poor breastfeeding (p=0,001; OR=6,469). Kata kunci: Stunting, Exclusive Breastfeeding, Complementary Feeding,Immunization